Leukoencephalopathy hypomyelination with brainstem and spinal cord involvement and leg spasticity caused by DARS1 mutations - Zhu, Jingyi; Guo, Xiaomin; Ran, Ningjing; Liang, Jingtao; Liu, Fuyou; Liu, Junyan; Wang, Rongyu; Jiang, Lianyan; Yang, Dongdong; Liu, Meijun (Frontiers in Genetics, 2023)
Hypomyelination with brainstem and spinal cord involvement and leg spasticity (HBSL), caused by aspartyl-tRNA synthetase (DARS1) gene mutations, is extremely rare, with only a few cases reported worldwide; thus, reports on HBSL treatment are few. In this review, we summarized the clinical manifestations, imaging features, treatment methods, and gene mutations responsible for HBSL based on relevant studies and cases.